Dampak Pembelajaran Kewirausahaan Berbasis Artificial Intelligence (AI) terhadap Minat Bisnis Digital Mahasiswa - Zenadia Luisa Madalena da Costa Sousa; Petrus Alexandro Kelen; Betzy Cleodiva Moyna Djawa; Pascarlio Yoseph Zawa; Dani Alexander Ria; Enike Tje Yustin Dima (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the impact of Artificial Intelligence (AI)-based entrepreneurship learning on students’ interest in digital business. The rapid development of digital technology has transformed entrepreneurship education, requiring learning approaches that are more adaptive, innovative, and aligned with the demands of the digital economy. This study employed a qualitative approach using a literature review method by examining various scientific journals and relevant references related to entrepreneurship, Artificial Intelligence, digital learning, and digital business. The findings indicate that integrating AI into entrepreneurship learning enhances students’ understanding of entrepreneurial concepts, stimulates creativity and innovation, and improves analytical skills in identifying and evaluating business opportunities. Furthermore, AI-supported learning increases students’ motivation, self-confidence, and readiness to establish digital businesses by providing interactive learning experiences and data-driven decision-making support. AI-based entrepreneurship education also encourages the development of critical thinking, problem-solving abilities, and digital competencies needed in the modern business environment. Nevertheless, the effective implementation of AI in entrepreneurship learning requires adequate digital literacy, technological infrastructure, and ethical awareness to ensure responsible and sustainable technology use. This study concludes that AI-based entrepreneurship learning represents a strategic educational approach for cultivating adaptive, innovative, and competitive human resources while fostering students’ interest and readiness to engage in digital entrepreneurship in the era of digital transformation.